(untitled) (Research, Society and Development, 2021)
The teaching of Human Anatomy still uses the traditional model, contentist, focused on memorization, making it uninteresting from the students’ perspective. This work aims to present pedagogical innovations, built from the use of active learning methodologies and digital tools for Physical Education graduates. Research was carried out to ascertain educational trends for the 21st century. The following trends were incorporated: hybrid teaching, inverted classroom and gamification. For this, a Multimodal Hybrid Teaching Environment was created containing three online environments (Moodle platform, Facebook and Instagram) and two offline environments (theoretical classroom and practical laboratory). In addition, anatomical contents were approached in a systemic, multimodal, interdisciplinary manner and with a focus on professional practice. It is hoped that the proposal presented can contribute to the teaching and learning of Anatomy for undergraduate Physical Education students.